Experiences of violence and moral reasoning in a context of vengeance/ experiencias de violencia y razonamiento moral en un contexto de venganza/ experiências de violência e racionamento moral em um contexto... (2012)
Relations between exposure to violence and moral reasoning were explored. Ninety-six participants aged 6-16 years evaluated the acceptability of stealing and causing physical harm in a situation of vengeance. Self-reports of exposure to violence were collected from each participant. Findings indicated that previous exposure to violence is related to moral reasoning in contexts of vengeance. Participants who reported having witnessed more violence, especially against family members, evaluated causing physical harm more positively, provided justifications entailing retaliation more frequently, and offered fewer reasons related to the conventional and personal realms, in a context of vengeance. Moreover, witnessing particular violent events was found to be positively correlated with judgments justified with reasons involving retaliation. These results suggest that participants think of vengeance as a way to restore justice (a moral issue) through expiatory sanction.